If x=1/4-√15 , y=1/4+√15 then x cube + y cube =
Answers
Answered by
34
Given,
![x = \frac{1}{4 - \sqrt{15} } x = \frac{1}{4 - \sqrt{15} }](https://tex.z-dn.net/?f=x+%3D++%5Cfrac%7B1%7D%7B4+-++%5Csqrt%7B15%7D+%7D+)
and,
![y = \frac{1}{4 + \sqrt{15} } y = \frac{1}{4 + \sqrt{15} }](https://tex.z-dn.net/?f=y+%3D++%5Cfrac%7B1%7D%7B4+%2B++%5Csqrt%7B15%7D+%7D+)
We have to find,
![{x}^{3} + {y}^{3} {x}^{3} + {y}^{3}](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B3%7D++%2B++%7By%7D%5E%7B3%7D+)
Finding :
![x = \frac{1}{4 - \sqrt{15} } x = \frac{1}{4 - \sqrt{15} }](https://tex.z-dn.net/?f=x+%3D++%5Cfrac%7B1%7D%7B4+-++%5Csqrt%7B15%7D+%7D+)
Rationalising the denominator,
![= > x = \frac{1}{4 - \sqrt{15} } \times \frac{4 + \sqrt{15} }{4 + \sqrt{15} } = > x = \frac{1}{4 - \sqrt{15} } \times \frac{4 + \sqrt{15} }{4 + \sqrt{15} }](https://tex.z-dn.net/?f=+%3D++%26gt%3B+x+%3D++%5Cfrac%7B1%7D%7B4+-++%5Csqrt%7B15%7D+%7D++%5Ctimes++%5Cfrac%7B4+%2B++%5Csqrt%7B15%7D+%7D%7B4+%2B++%5Csqrt%7B15%7D+%7D+)
![= > x = \frac{1 \times 4 + \sqrt{15} }{ ({4})^{2} - {( \sqrt{15}) }^{2} } = > x = \frac{1 \times 4 + \sqrt{15} }{ ({4})^{2} - {( \sqrt{15}) }^{2} }](https://tex.z-dn.net/?f=+%3D++%26gt%3B+x+%3D++%5Cfrac%7B1+%5Ctimes+4+%2B++%5Csqrt%7B15%7D+%7D%7B+%28%7B4%7D%29%5E%7B2%7D+-++%7B%28+%5Csqrt%7B15%7D%29+%7D%5E%7B2%7D++%7D+)
![= > x = \frac{4 + \sqrt{15} }{16 - 15} = > x = \frac{4 + \sqrt{15} }{16 - 15}](https://tex.z-dn.net/?f=+%3D++%26gt%3B+x+%3D++%5Cfrac%7B4+%2B++%5Csqrt%7B15%7D+%7D%7B16+-+15%7D+)
![= > x = \frac{4 + \sqrt{15} }{1} = > x = \frac{4 + \sqrt{15} }{1}](https://tex.z-dn.net/?f=+%3D++%26gt%3B+x+%3D++%5Cfrac%7B4++%2B++%5Csqrt%7B15%7D+%7D%7B1%7D+)
![= > x = 4 + \sqrt{15} \: \: \: = > x = 4 + \sqrt{15} \: \: \:](https://tex.z-dn.net/?f=+%3D++%26gt%3B+x+%3D+4+%2B++%5Csqrt%7B15%7D++%5C%3A++%5C%3A++%5C%3A)
Therefore, x = 4 + √15 (I)
Again,
![y = \frac{1}{4 + \sqrt{15} } y = \frac{1}{4 + \sqrt{15} }](https://tex.z-dn.net/?f=y+%3D++%5Cfrac%7B1%7D%7B4+%2B++%5Csqrt%7B15%7D+%7D+)
Rationalising the denominator,
![= > y = \frac{1}{4 + \sqrt{15} } \times \frac{4 - \sqrt{15} }{4 - \sqrt{15} } = > y = \frac{1}{4 + \sqrt{15} } \times \frac{4 - \sqrt{15} }{4 - \sqrt{15} }](https://tex.z-dn.net/?f=+%3D++%26gt%3B+y+%3D++%5Cfrac%7B1%7D%7B4+%2B++%5Csqrt%7B15%7D+%7D+%5Ctimes++%5Cfrac%7B4+-++%5Csqrt%7B15%7D+%7D%7B4+-++%5Csqrt%7B15%7D+%7D++)
![= > y = \frac{1 \times 4 - \sqrt{15} }{ ({4})^{2} - { (\sqrt{15} )}^{2} } = > y = \frac{1 \times 4 - \sqrt{15} }{ ({4})^{2} - { (\sqrt{15} )}^{2} }](https://tex.z-dn.net/?f=+%3D++%26gt%3B+y+%3D++%5Cfrac%7B1+%5Ctimes+4+-++%5Csqrt%7B15%7D+%7D%7B+%28%7B4%7D%29%5E%7B2%7D+-++%7B+%28%5Csqrt%7B15%7D+%29%7D%5E%7B2%7D++%7D+)
![= > y = \frac{4 - \sqrt{15} }{16 - 15} = > y = \frac{4 - \sqrt{15} }{16 - 15}](https://tex.z-dn.net/?f=+%3D++%26gt%3B+y+%3D++%5Cfrac%7B4+-++%5Csqrt%7B15%7D+%7D%7B16+-+15%7D+)
![= > y = \frac{4 - \sqrt{15} }{1} = > y = \frac{4 - \sqrt{15} }{1}](https://tex.z-dn.net/?f=+%3D++%26gt%3B+y+%3D++%5Cfrac%7B4+-++%5Csqrt%7B15%7D+%7D%7B1%7D+)
![= > y = 4 - \sqrt{15} = > y = 4 - \sqrt{15}](https://tex.z-dn.net/?f=+%3D++%26gt%3B+y+%3D+4+-++%5Csqrt%7B15%7D+)
Therefore, y = 4 - √15. (II)
Now,
x + y
= (4 + √15) + (4 - √15)
= 4 + √15 + 4 - √15
= 4 + 4 + 0
= 8
Further,
xy
= (4 + √15) (4 - √15)
= 16 + 4√15 - 4√15 - 15
= 16 - 15
= 1
Now, we know that,
![{x}^{3} + {y}^{3} = (x + y)( {x}^{2} + {y}^{2} - xy) {x}^{3} + {y}^{3} = (x + y)( {x}^{2} + {y}^{2} - xy)](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B3%7D+++%2B++%7By%7D%5E%7B3%7D++%3D+%28x+%2B+y%29%28+%7Bx%7D%5E%7B2%7D+++%2B+%7By%7D%5E%7B2%7D+++-++xy%29)
![= (8)({4 + \sqrt{15}})^{2}+ {(4 - \sqrt{15} })^{2} - 1 = (8)({4 + \sqrt{15}})^{2}+ {(4 - \sqrt{15} })^{2} - 1](https://tex.z-dn.net/?f=+%3D+%288%29%28%7B4+%2B++%5Csqrt%7B15%7D%7D%29%5E%7B2%7D%2B+%7B%284+-++%5Csqrt%7B15%7D+%7D%29%5E%7B2%7D++-+1)
![= (8)(16 + 15) + (16 - 15) - (1) = (8)(16 + 15) + (16 - 15) - (1)](https://tex.z-dn.net/?f=+%3D+%288%29%2816+%2B+15%29+%2B+%2816+-+15%29+-+%281%29)
![= (8)(31) + (1) - (1) = (8)(31) + (1) - (1)](https://tex.z-dn.net/?f=+%3D+%288%29%2831%29+%2B+%281%29+-+%281%29)
![= 8 \times 31 = 8 \times 31](https://tex.z-dn.net/?f=+%3D+8+%5Ctimes+31)
![= 248 = 248](https://tex.z-dn.net/?f=+%3D+248)
That's your answer.
Hope it'll help.. :-D
and,
We have to find,
Finding :
Rationalising the denominator,
Therefore, x = 4 + √15 (I)
Again,
Rationalising the denominator,
Therefore, y = 4 - √15. (II)
Now,
x + y
= (4 + √15) + (4 - √15)
= 4 + √15 + 4 - √15
= 4 + 4 + 0
= 8
Further,
xy
= (4 + √15) (4 - √15)
= 16 + 4√15 - 4√15 - 15
= 16 - 15
= 1
Now, we know that,
That's your answer.
Hope it'll help.. :-D
anonymous64:
If it was helpful to you, please mark as Brainliest.
Answered by
6
Given,
and,
We have to find,
Finding :
Rationalising the denominator,
Therefore, x = 4 + √15 (I)
Again,
Rationalising the denominator,
Therefore, y = 4 - √15. (II)
Now,
x + y
= (4 + √15) + (4 - √15)
= 4 + √15 + 4 - √15
= 4 + 4 + 0
= 8
Further,
xy
= (4 + √15) (4 - √15)
= 16 + 4√15 - 4√15 - 15
= 16 - 15
= 1
Now, we know that,
248....
That's your answer.
and,
We have to find,
Finding :
Rationalising the denominator,
Therefore, x = 4 + √15 (I)
Again,
Rationalising the denominator,
Therefore, y = 4 - √15. (II)
Now,
x + y
= (4 + √15) + (4 - √15)
= 4 + √15 + 4 - √15
= 4 + 4 + 0
= 8
Further,
xy
= (4 + √15) (4 - √15)
= 16 + 4√15 - 4√15 - 15
= 16 - 15
= 1
Now, we know that,
248....
That's your answer.
Similar questions
Social Sciences,
8 months ago
Hindi,
8 months ago
Social Sciences,
8 months ago
English,
1 year ago
Chemistry,
1 year ago
Social Sciences,
1 year ago